Development of a time-dependent numerical model for the assessment of non-stationary pharyngoesophageal tissue vibrations after total laryngectomy - Hüttner, Björn; Luegmair, Georg; Patel, Rita R.; Ziethe, Anke; Eysholdt, Ulrich; Bohr, Christopher; Sebova, Irina; Semmler, Marion; Döllinger, Michael (Biomechanics and Modeling in Mechanobiology, 2015)
Laryngeal cancer due to, e.g., extensive smoking and/or alcohol consumption can necessitate the excision of the entire larynx. After such a total laryngectomy, the voice generating structures are lost and with that the quality of life of the concerning patients is drastically reduced. However, the vibrations of the remaining tissue in the so called pharyngoesophageal (PE) segment can be applied as alternative sound generator. Tissue, scar, and geometric aspects of the PE-segment determine the postoperative substitute voice characteristic, being highly important for the future live of the patient. So far, PE-dynamics are simulated by a biomechanical model which is restricted to stationary vibrations, i.e., variations in pitch and amplitude cannot be handled. In order to investigate the dynamical range of PE-vibrations, knowledge about the temporal processes during substitute voice production is of crucial interest. Thus, time-dependent model parameters are suggested in order to quantify non-stationary PE-vibrations and drawing conclusions on the temporal characteristics of tissue stiffness, oscillating mass, pressure, and geometric distributions within the PE-segment. To adapt the numerical model to the PE-vibrations, an automatic, block-based optimization procedure is applied, comprising a combined global and local optimization approach. The suggested optimization procedure is validated with 75 synthetic data sets, simulating non-stationary oscillations of differently shaped PE-segments. The application to four high-speed recordings is shown and discussed. The correlation between model and PE-dynamics is [Formula: see text] 97 %.
EVALuna2:19926